PENDIDIKAN NILAI-NILAI KRISTEN DALAM MEMBANGUN BUDAYA YANG MENGHORMATI KEBERAGAMAN BAGI MASYARAKAT PLURAL - Diany Rita Pangapulon Saragih; John David Simatupang; Hotman Siagian (Institut Agama Kristen Negeri Kupang, 2023)
Untreated diversity can be a trigger for tension and a source of conflict. Building a culture that respects diversity by strengthening Christian values instilled in families, schools and churches can become the foundation of life in a pluralistic society in Indonesia. Christian values should become the practice of faith in life. This research uses a descriptive qualitative approach by collecting references through literature studies so that this article produces explanations that are discussed systematically. Christian values education plays a role in building a culture that respects diversity. This research can be interpreted that Christian values contribute to caring for and maintaining diversity in Indonesian society.. but also the teaching of Christian values plays a role in building spirituality, integrity, loyalty in order to maintain Christian faith in the midst of plurality diversity.